Araguazetes luisi gen. nov., sp. nov. (Acari, Oribatida, Haplozetidae) from Henri Pittier National Park, Venezuela - Ermilov, Sergey G.; Behan-Pelletier, Valerie M. (Zootaxa, 2024)
A new oribatid mite genus, Araguazetes gen. nov. (Oribatida, Haplozetidae), with type species Araguazetes luisi sp. nov., is proposed and described from Henri Pittier National Park, Venezuela. Based on an analysis of adults of genera of Haplozetidae, the new genus is closely related to Haplozetes and Mancoribates, from which it is most easily distinguished by the broad, nearly rounded notogaster, the adjacent dorsal position of the rostral setae, the arch-like translamella, and the absence of the interlamellar setae and their alveoli. Relationships between Araguazetes and selected other genera within Haplozetidae are discussed.